2017
DOI: 10.2147/copd.s127923
|View full text |Cite
|
Sign up to set email alerts
|

Pre- and post-bronchodilator airway obstruction are associated with similar clinical characteristics but different prognosis – report from a population-based study

Abstract: IntroductionAccording to guidelines, the diagnosis of COPD should be confirmed by post-bronchodilator (post-BD) airway obstruction on spirometry; however, in clinical practice, this is not always performed. The aim of this population-based study was to compare clinical characteristics and prognosis, assessed as mortality, between subjects with airway obstruction divided into pre- but not post-BD obstruction, post-BD airway obstruction (COPD), and subjects without airway obstruction.Materials and methodsIn 2002… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
12
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 36 publications
2
12
0
Order By: Relevance
“…The positive predictive value of AO for AO post-BD was lower in women than in men in our sample, which could be explained by differences among the subjects with AO. As reported by Sawalha and colleagues 5 , we also found that the percentage of ever smokers (79.7% vs 73.4%), the median number of lifetime pack-years (25 vs 20), and the percentage of subjects with productive cough (21.0% vs 14.5%), factors that may predict the occurrence of COPD 14 , were higher in men than in women with AO and valid post-bronchodilator spirometry at the 3 rd examination. In addition, our estimates of the positive predictive value (59.1% in males and 42.6% in females) were lower than the figure obtained by Schermer and colleagues (74.7% in both sexes) when the fixed cut-off definition of AO was used 4 .…”
Section: N° Of Subjectsmentioning
confidence: 59%
See 1 more Smart Citation
“…The positive predictive value of AO for AO post-BD was lower in women than in men in our sample, which could be explained by differences among the subjects with AO. As reported by Sawalha and colleagues 5 , we also found that the percentage of ever smokers (79.7% vs 73.4%), the median number of lifetime pack-years (25 vs 20), and the percentage of subjects with productive cough (21.0% vs 14.5%), factors that may predict the occurrence of COPD 14 , were higher in men than in women with AO and valid post-bronchodilator spirometry at the 3 rd examination. In addition, our estimates of the positive predictive value (59.1% in males and 42.6% in females) were lower than the figure obtained by Schermer and colleagues (74.7% in both sexes) when the fixed cut-off definition of AO was used 4 .…”
Section: N° Of Subjectsmentioning
confidence: 59%
“…spirometry, and the use of pre-bronchodilator measurements may lead to some misclassification of the disease 5 . However, post-bronchodilator spirometry has been adopted in epidemiological studies in recent years only.…”
mentioning
confidence: 99%
“…Indeed, the change in approach by GOLD was based on the observation that FEV 1 alone is not a strong predictor of exacerbation risk; consequently pharmacotherapy recommendations are now based on exacerbations and symptoms alone [6]. In view of the link between exacerbation risk and comorbidities, the revised approach is also in line with previous observations that spirometry alone does not correlate strongly with individual comorbidities [19,20]. Comorbidities definitely play a role in the impact and burden COPD, with cardiovascular events being one of the main causes of mortality [21,22].…”
Section: Symptoms Exacerbationsmentioning
confidence: 89%
“…This was an unexpected finding and we cannot explain this difference between the countries. However, it has been argued that there are differences in clinical presentation between men and women with COPD, where for instance women present with more dyspnea but less sputum production than men (51,52). The prevalence of sputum production was similar among men and women in all the four study areas, while the prevalence of dyspnea was higher among women than among men.…”
Section: Discussionmentioning
confidence: 88%